2009
DOI: 10.1002/aic.12123
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of mass transfer velocity based on measured turbulence parameters

Abstract: in Wiley InterScience (www.interscience.wiley.com).The aim of this study is to quantify the mass transfer velocity using turbulence parameters from simultaneous measurements of oxygen concentration fields and velocity fields. The surface divergence model was considered in more detail, using data obtained for the lower range of b (surface divergence). It is shown that the existing models that use the divergence concept furnish good predictions for the transfer velocity also for low values of b, in the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 41 publications
(56 reference statements)
4
46
0
1
Order By: Relevance
“…Back to vertical phenomenon considerations, it has been observed by Herlina and Jirka [5,8] and Janzen et al [10], and confirmed by Variano and Cowen [6,12] that surface renewal is not the only mechanism responsible for turbulent mass transfer.…”
Section: Mass Transfer Modelsmentioning
confidence: 85%
See 3 more Smart Citations
“…Back to vertical phenomenon considerations, it has been observed by Herlina and Jirka [5,8] and Janzen et al [10], and confirmed by Variano and Cowen [6,12] that surface renewal is not the only mechanism responsible for turbulent mass transfer.…”
Section: Mass Transfer Modelsmentioning
confidence: 85%
“…This smaller scale convection like phenomena, also called "injection" events, were found to be not only observable [10,16] but also quantitatively non negligible in the total mass flux exchanged [12]. Mass transfer seems therefore to be enhanced by a combination of injection and renewal events at different scales.…”
Section: Mass Transfer Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This simultaneous measurement was extensively used to investigate the mixing processes [17] [18] [19]. Figure 3 shows the measurement section of simultaneous PIV and PLIF measurement.…”
Section: Methodsmentioning
confidence: 99%